Anatomy of a Lynching : The Killing of Claude Neal - McGovern, James R. (Book collections on Project MUSE., 2014)
"First published in 1982, James R. McGovern's Anatomy of a Lynching unflinchingly reconstructs the grim events surrounding the death of Claude Neal, one of the estimated three thousand blacks who died at the hands of southern lynch mobs in the six decades between the 1880s and the outbreak of World War II."--Back cover.